A Facile Synthesis of Chiral Isocyanate-phenol and Unsymmetrical Urea Derived from Tyrosines without Protecting Phenolic Hydroxyl Groups - Nagai, Atsushi; Ochiai, Bungo; Endo, Takeshi (Letters in Organic Chemistry, 2005)
A facile method for synthesis and isolation of chiral isocyanate-phenols, obtained from the reactions of L-tyrosine and L-DOPA [L-3-(3,4-dihydroxyphenyl)alanine] derivatives with di-tert-butyltricarbonate (DBTC), is described. Reaction of the obtained isocyanate-phenol with n-butylamine gave the corresponding chiral unsymmetrical urea.
Keywords: isocyanate